FORMULATION AND EVALUATION OF LIDOCAINE HYDROCHLORIDE CHEWABLE TABLET - Kasar, Harshada Anil; Dev, Asish; Dhal, Subhakanta (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to formulate and optimize a chewable formulation of lidocaine hydrochloride using a 32 factorial design for optimized the superdisintegrant concentration. Methods: Various concentrations of sodium starch glycolate (SSG) (13.33 mg, 26.66 mg, and 40 mg) of superdisintegrant and starch (50 mg, 83 mg, and 116.66 mg) were added in the formulation; nine formulations were prepared according to 32 factorial designs and evaluated. The responses were analyzed for analysis of variance using Design-Expert version 10 software. Statistical models were generated for each response parameter. The models were tested for significance. Procedure to manufacture chewable tablets by direct compression was established. Results: The results show that the presence of a superdisintegrant is desirable for chewable formulation. The best-optimized batch F7 found the batch having starch of amount 116.66 mg and SSG 13.33 mg. All the prepared batches of tablets were within the range. Optimized batch F7 showed drug content 102.46±0.0543, wetting time 18±1.7320, friability 0.65±0.0216, and drug release rate 99.97±0.0124% at the end of 30 min. Conclusion: It can be concluded that 32 full factorial design and statistical models can be successfully used to optimize the formulations, and it was concluded that the trial batch F7 is the optimized formulation which compiles official specifications of chewable tablets. The optimized batch was evaluated for thickness, weight variation, hardness, friability, drug dissolution, and stability study for 3 months. The similarity factor was calculated for comparison of dissolution profile before and after stability studies. After 30 min the drug release rate for batch F7 was 98.97% (Table 6). Hence, the results of stability studies reveal that the developed formulation has good stability.